Three-dimensional porous copper and preparation method thereof

By using corrosion liquid with neutral salt and weak acid complexing agent for electrochemical corrosion, the problems of low porosity and many cracks in the preparation of three-dimensional porous copper are solved, and three-dimensional porous copper with high porosity and low cracks are achieved, which improves battery performance.

CN119710887APending Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311278003.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing three-dimensional porous copper preparation methods, low porosity and many surface cracks affect the battery performance.

Method used

The corrosion liquid containing neutral salt and weak acid complexing agent is used for electrochemical corrosion, adjust the molar concentration ratio of the corrosion liquid, provide a stable corrosion environment, and reduce hole blockage and crack problems.

Benefits of technology

The porosity of three-dimensional porous copper is improved, crack formation is reduced, and the electrochemical performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710887A_ABST
    Figure CN119710887A_ABST
Patent Text Reader

Abstract

The invention discloses three-dimensional porous copper and a preparation method thereof.The preparation method of the three-dimensional porous copper comprises the following steps that a copper alloy matrix is provided, the copper alloy matrix comprises a Cu element and a non-Cu metal element, and the standard electrode potential of the non-Cu metal element is smaller than that of the Cu element; a corrosive liquid is provided, the corrosive liquid comprises neutral salt, a weakly acidic complexing agent and a solvent, the molar concentration of the neutral salt is recorded as C1, the molar concentration of the weakly acidic complexing agent is recorded as C2, the unit is mol / L, C2 / C1 is larger than or equal to 0.04 and smaller than or equal to 0.60, and C2 is smaller than or equal to 0.20 mol / L; and the copper alloy matrix is subjected to electrochemical corrosion with the corrosive liquid as electrolyte, and the three-dimensional porous copper is obtained. The porosity of the three-dimensional porous copper can be improved, and cracks of the three-dimensional porous copper can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a three-dimensional porous copper and a preparation method thereof. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in consumer electronics, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. The negative electrode is an important component of the battery, which will affect the performance of the battery. At present, the negative electrode of the battery is usually formed by setting a negative electrode film layer including negative electrode active materials such as graphite on a copper foil. However, with the continuous expansion of battery application fields, people's demand for high energy density batteries is increasing. Metal batteries and negative electrode-free batteries do not use negative electrode film layers, so they can have high energy density, but the uneven deposition and dendrite problems of metals restrict the development of metal batteries and negative electrode-free batteries. As an important component of metal batteries and negative electrode-free batteries, the negative electrode current collector is expected to alleviate the uneven deposition and dendrite problems of metals by improving it.

[0003] Three-dimensional porous copper has the advantages of light weight and large specific surface area. When used in batteries, it can improve the energy density of the battery and improve the reliability of the battery. Especially when used in metal batteries and negative electrode-free batteries, when the negative electrode adopts a three-dimensional porous copper structure, it can also reduce the problem of uneven metal deposition and dendrite problems. Electrochemical corrosion (i.e., electrochemical dealloying) of the copper alloy matrix is ​​a powerful method for preparing a three-dimensional porous copper structure. At present, the three-dimensional porous copper structure prepared by the dealloying process has problems such as low porosity and many surface cracks, so when it is used as a battery current collector, it will affect the performance of the battery.

[0004] The above statements are only used to provide background information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0005] The present application provides a three-dimensional porous copper and a preparation method thereof, which can improve the porosity of the three-dimensional porous copper and reduce cracks in the three-dimensional porous copper.

[0006] In a first aspect, the present application provides a method for preparing three-dimensional porous copper, comprising the following steps: providing a copper alloy substrate, wherein the copper alloy substrate comprises a Cu element and a non-Cu metal element, wherein the standard electrode potential of the non-Cu metal element is less than the standard electrode potential of the Cu element; providing a corrosive solution, wherein the corrosive solution comprises a neutral salt, a weakly acidic chelating agent and a solvent, wherein the molar concentration of the neutral salt is denoted as C1, and the molar concentration of the weakly acidic chelating agent is denoted as C2, both in units of mol / L, 0.04≤C2 / C1≤0.60, and C2 is less than or equal to 0.20 mol / L; and electrochemically corroding the copper alloy substrate using the corrosive solution as an electrolyte to obtain three-dimensional porous copper.

[0007] The etching solution provided in the embodiment of the present application can provide a stable corrosion environment, reduce the precipitation reaction of metal ions dissolved during the electrochemical dealloying process, thereby reducing the pore blocking problem and surface passivation problem of the prepared three-dimensional porous copper, and further improve the porosity of the prepared three-dimensional porous copper structure; at the same time, it can also reduce crack formation.

[0008] The three-dimensional porous copper obtained by the preparation method provided in the embodiment of the present application can have a high porosity and fewer cracks, so when applied to a battery current collector, the electrochemical performance of the battery can be improved.

[0009] In some embodiments, 0.10≤C2 / C1≤0.24. By further adjusting C2 / C1 within the above range, the porosity of the prepared three-dimensional porous copper structure can be further improved, and crack formation can be reduced.

[0010] In some embodiments, C1 is 0.2 mol / L-2.0 mol / L, and can be 0.5 mol / L-1.5 mol / L. By further adjusting the molar concentration C1 of the neutral salt within the above range, the reaction rate of electrochemical dealloying can be increased, the porosity of the prepared three-dimensional porous copper structure can be increased, and crack formation can be reduced.

[0011] In some embodiments, C2 is 0.04mol / L-0.20mol / L, and can be optionally 0.08mol / L-0.16mol / L. By further adjusting the molar concentration C2 of the weakly acidic complexing agent within the above range, the pore blocking problem and surface passivation problem of the prepared three-dimensional porous copper can be further reduced, the porosity of the prepared three-dimensional porous copper structure can be increased, and the formation of hydrogen embrittlement cracks can be further reduced.

[0012] In some embodiments, the neutral salt includes one or more of sodium salt and potassium salt, and may optionally include one or more of sodium chloride and potassium chloride.

[0013] In some embodiments, the weakly acidic chelating agent includes one or more of dicarboxylic acids, polycarboxylic acids, and their respective salts, and can be optionally citric acid, isocitric acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, fumaric acid, and their respective salts. Optionally, the salt includes one or more of sodium salt, potassium salt, sodium-potassium salt, and ammonium salt.

[0014] By further adjusting the weakly acidic complexing agent within the above range, the porosity of the prepared three-dimensional porous copper structure can be further improved, and crack formation can also be reduced.

[0015] In some embodiments, the solvent comprises water.

[0016] In some embodiments, a three-electrode system is used to electrochemically corrode the copper alloy substrate using the corrosive solution as an electrolyte, the copper alloy substrate is a working electrode, the AgCl / Ag electrode is a reference electrode, and the platinum electrode is a counter electrode.

[0017] In some embodiments, the voltage between the copper alloy substrate and the reference electrode is -0.70V to -0.15V.

[0018] In some embodiments, the temperature for electrochemically corroding the copper alloy substrate using the corrosive solution as an electrolyte is 10°C-65°C, and can be optionally 20°C-35°C.

[0019] In some embodiments, the time for electrochemically corroding the copper alloy substrate using the corrosive solution as the electrolyte is 3 hours to 24 hours, and can be optionally 6 hours to 10 hours.

[0020] In some embodiments, the copper alloy substrate is in the form of a sheet or foil.

[0021] In some embodiments, the non-Cu metal element includes one or more of Mn, Zn, Ni, Al, and Fe.

[0022] In some embodiments, the preparation method further includes the step of: rinsing the copper alloy substrate with a corrosive solution.

[0023] In some embodiments, the preparation method further comprises the steps of: washing the three-dimensional porous copper after electrochemical corrosion with water, washing with alcohol and drying. The water washing can remove the soluble salt in the three-dimensional porous copper structure, and the alcohol washing can remove the residual water in the three-dimensional porous copper structure.

[0024] In some embodiments, the atomic percentage of the non-Cu metal elements in the copper alloy matrix is ​​greater than 65 at.%, and may be 65 at.%-80 at.%. Thus, when the prepared three-dimensional porous copper is applied to a battery current collector, the electrochemical performance of the battery can be better improved.

[0025] The second aspect of the present application provides a three-dimensional porous copper, which is prepared by the preparation method of the first aspect of the present application.

[0026] In some embodiments, the pore diameter of the three-dimensional porous copper is 0.3 μm-20 μm, and can be 2 μm-8 μm.

[0027] In some embodiments, the ligament width of the three-dimensional porous copper is 0.5 μm-20 μm, and optionally 2 μm-8 μm.

[0028] In some embodiments, the non-Cu metal residue in the three-dimensional porous copper is less than or equal to 5 at.%, and may be less than or equal to 2 at.%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Example 1 is shown.

[0030] Figure 2 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Example 13 is shown.

[0031] Figure 3 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Example 16 is shown.

[0032] Figure 4 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 1 is shown.

[0033] Figure 5 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 2 is shown.

[0034] Figure 6 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 3 is shown.

[0035] Figure 7 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 4 is shown.

[0036] Figure 8 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 5 is shown.

[0037] Fig. 9 A scanning electron microscope (SEM) image of the three-dimensional porous copper prepared in Comparative Example 6 is shown. DETAILED DESCRIPTION

[0038] Hereinafter, the three-dimensional porous copper and the method for preparing the same of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0039] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0040] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0041] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0042] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0043] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0044] In the description of the embodiments of the present application, unless otherwise specified, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, a first feature being “above”, “above”, or “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, or “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0045] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0046] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0047] The embodiment of the present application provides a method for preparing three-dimensional porous copper.

[0048] The preparation method comprises the following steps: providing a copper alloy substrate, the copper alloy substrate comprises a Cu element and a non-Cu metal element, the standard electrode potential of the non-Cu metal element is less than the standard electrode potential of the Cu element; providing a corrosive solution, the corrosive solution comprises a neutral salt, a weakly acidic complexing agent and a solvent, the molar concentration of the neutral salt is recorded as C1, the molar concentration of the weakly acidic complexing agent is recorded as C2, both in mol / L, 0.04≤C2 / C1≤0.60, and C2 is less than or equal to 0.20 mol / L; electrochemically corroding the copper alloy substrate with the corrosive solution as an electrolyte to obtain three-dimensional porous copper.

[0049] At present, when a three-dimensional porous copper structure is prepared by a dealloying process, the etching liquid used is mainly a strong acid (such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, etc.) solution, a strong alkali (such as sodium hydroxide, potassium hydroxide, etc.) solution, a neutral salt (such as sodium chloride, etc.) solution, or a mixed solution of a strong acid and a neutral salt. However, the above etching solutions all have certain defects.

[0050] When the corrosive liquid is a strong alkaline solution or a neutral salt solution, the acidity and alkalinity of the corrosive liquid are difficult to control, which makes it easy for the metal ions dissolved from the copper alloy matrix to form solid metal compound particles and adsorb on the surface of the formed three-dimensional porous copper structure, which easily causes pore blocking and surface passivation problems, and then causes the porosity of the prepared three-dimensional porous copper structure to be much lower than the theoretical value (i.e., the theoretical value of the porosity after the copper alloy matrix is ​​completely dealloyed). In addition, since the surface of the three-dimensional porous copper structure is covered with solid metal compound particles, the presence of solid metal compound particles will also hinder the further modification of the three-dimensional porous copper structure, for example, it will hinder the lithiation treatment of the three-dimensional porous copper structure, and then when applied to batteries, it is difficult to effectively improve the performance of the battery.

[0051] When the corrosive liquid is a strong acid solution or a mixed solution of a strong acid and a neutral salt, the prepared three-dimensional porous copper structure is prone to cracks during electrochemical corrosion. When used in batteries, the crack structure is likely to aggravate the uneven deposition of the metal, thereby affecting the performance of the battery.

[0052] The etching solution provided in the embodiment of the present application includes a neutral salt and a weakly acidic chelating agent, and the molar concentration C1 of the neutral salt and the molar concentration C2 of the weakly acidic chelating agent also satisfy 0.04≤C2 / C1≤0.60 and C2 is less than or equal to 0.20 mol / L.

[0053] During the electrochemical dealloying process, the non-Cu metal in the copper alloy matrix loses electrons, and the electrons flow to the counter electrode through the external circuit. The hydrogen ions near the counter electrode gain electrons to produce hydrogen. At the same time, the etching solution between the counter electrode and the working electrode acts as a conductive solution, which contributes ionic conductivity to allow the current to flow smoothly.

[0054] The neutral salt in the etching solution itself does not participate in the electrochemical reaction, so its concentration can be maintained relatively stable during the electrochemical dealloying process, and the electrochemical dealloying effect will not be affected by the change in the concentration of the etching solution. The molar concentration C1 of the neutral salt and the molar concentration C2 of the weakly acidic complexing agent satisfy C2 / C1 less than or equal to 0.60. Compared with the weakly acidic complexing agent, the molar concentration of the neutral salt is higher, thereby providing a sufficiently large and stable ionic conductivity for the working circuit of the electrochemical dealloying, so that the current of the working circuit can be unblocked.

[0055] Weakly acidic complexing agents can provide hydrogen ions for the reduction half-reaction on the electrode, thereby maintaining the weak acidity of the corrosive solution. As hydrogen ions are consumed, a large number of free acid radical ions can also act as complexing agents, thereby reducing or even inhibiting the precipitation reaction of metal ions dissolved during the dealloying process. In addition, they can also complex the metal ions dissolved during the dealloying process and promote the forward corrosion reaction.

[0056] The molar concentration C1 of the neutral salt and the molar concentration C2 of the weakly acidic complexing agent satisfy C2 / C1 greater than or equal to 0.04, which helps to reduce the precipitation reaction of the metal ions dissolved during the electrochemical dealloying process, thereby reducing the pore blocking problem and surface passivation problem, and further improves the porosity of the prepared three-dimensional porous copper structure. During the electrochemical dealloying process, the electrode will continuously consume hydrogen ions due to hydrogen evolution. When C2 / C1 is less than 0.04, the corrosive liquid near the electrode is easy to turn alkaline. At the same time, after the corrosive liquid in this area diffuses near the working electrode, it is also easy to make the metal ions dissolved from the copper alloy matrix form solid metal compound particles and adsorb on the surface of the formed three-dimensional porous copper structure, which is easy to cause pore blocking and surface passivation problems, and also reduce the porosity of the prepared three-dimensional porous copper structure, and its porosity is usually much lower than the theoretical value.

[0057] The molar concentration C2 of the weakly acidic complexing agent also needs to be less than or equal to 0.20 mol / L, thereby reducing the formation of hydrogen embrittlement cracks. When the molar concentration C2 of the weakly acidic complexing agent is greater than 0.20 mol / L, the hydrogen ion concentration at the dealloying interface is too high, which easily causes a violent chemical dealloying reaction, thereby easily leading to the formation of hydrogen embrittlement cracks.

[0058] Therefore, the etching solution provided in the embodiment of the present application can provide a stable corrosion environment, reduce the precipitation reaction of metal ions dissolved during the electrochemical dealloying process, thereby reducing the pore blocking problem and surface passivation problem of the prepared three-dimensional porous copper, and further improve the porosity of the prepared three-dimensional porous copper structure; at the same time, it can also reduce crack formation.

[0059] The three-dimensional porous copper obtained by the preparation method provided in the embodiment of the present application can have a high porosity and fewer cracks, so when applied to a battery current collector, the electrochemical performance of the battery can be improved.

[0060] C2 / C1 can be 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.24, 0.30, 0.40, 0.50, 0.60, or any range thereof. In some embodiments, optionally, 0.06≤C2 / C1≤0.40, 0.08≤C2 / C1≤0.30, 0.10≤C2 / C1≤0.24, 0.10≤C2 / C1≤0.20, 0.10≤C2 / C1≤0.16.

[0061] By further adjusting C2 / C1 within the above range, the porosity of the prepared three-dimensional porous copper structure can be further improved and crack formation can be reduced.

[0062] In some embodiments, the molar concentration C2 of the weakly acidic complexing agent can be 0.04mol / L-0.20mol / L, for example, it can be 0.04mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.10mol / L, 0.11mol / L, 0.12mol / L, 0.13mol / L, 0.14mol / L, 0.15mol / L, 0.16mol / L, 0.17mol / L, 0.18mol / L, 0.19mol / L, 0.20mol / L, or a range consisting of any of the above values. Optionally, the molar concentration C2 of the weakly acidic complexing agent can be 0.08mol / L-0.16mol / L.

[0063] By further adjusting the molar concentration C2 of the weakly acidic complexing agent within the above range, the pore blocking problem and surface passivation problem of the prepared three-dimensional porous copper can be further reduced, the porosity of the prepared three-dimensional porous copper structure can be improved, and the formation of hydrogen embrittlement cracks can be further reduced.

[0064] In some embodiments, the molar concentration C1 of the neutral salt can be 0.2mol / L-2.0mol / L, for example, it can be 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, or a range consisting of any of the above values. Optionally, the molar concentration C1 of the neutral salt can be 0.5mol / L-1.5mol / L.

[0065] By further adjusting the molar concentration C1 of the neutral salt within the above range, the reaction rate of electrochemical dealloying can be increased, the porosity of the prepared three-dimensional porous copper structure can be increased, and crack formation can be reduced.

[0066] In some embodiments, the copper alloy substrate may be in sheet or foil form.

[0067] The copper alloy matrix includes Cu element and non-Cu metal elements, and the atomic mass ratio of the Cu element and the non-Cu metal elements is not specifically limited and can be adjusted according to the required porosity of the three-dimensional porous copper structure.

[0068] In some embodiments, the atomic percentage of non-Cu metal elements in the copper alloy matrix may be greater than 65 at.%, and may be 65 at.%-80 at.%, and may be 70 at.%-75 at.%. Thus, when the prepared three-dimensional porous copper is applied to a battery current collector, the electrochemical performance of the battery can be better improved.

[0069] In some embodiments, the non-Cu metal elements in the copper alloy matrix may include one or more of Mn, Zn, Ni, Al, and Fe.

[0070] In some embodiments, the copper alloy matrix may further include non-metallic elements, such as C, Si, etc.

[0071] The copper alloy substrate can be purchased from the market, or prepared according to methods known in the art, for example, by a smelting method.

[0072] In some embodiments, the molar amount of the weakly acidic complexing agent in the etching solution may be more than twice the molar amount of the non-Cu metal element in the copper alloy matrix, and may be 2 to 8 times.

[0073] In some embodiments, the neutral salt in the corrosive solution may include one or more of sodium salt and potassium salt, and may optionally include one or more of sodium chloride and potassium chloride.

[0074] The complexing effect of the weakly acidic complexing agent generally refers to the fact that the weakly acidic complexing agent can complex the non-Cu metal ions dissolved from the copper alloy matrix. In some embodiments, the weakly acidic complexing agent in the etching solution can include one or more of dicarboxylic acids, polycarboxylic acids, and their respective salts.

[0075] Optionally, the weakly acidic complexing agent in the etching solution may include one or more of citric acid, isocitric acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, fumaric acid, and their respective salts.

[0076] Optionally, the salts of the above-mentioned dicarboxylic acids and polycarboxylic acids may include one or more of sodium salt, potassium salt, sodium-potassium salt and ammonium salt.

[0077] By further adjusting the weakly acidic complexing agent within the above range, the porosity of the prepared three-dimensional porous copper structure can be further improved, and crack formation can also be reduced.

[0078] In some embodiments, the solvent in the etching solution may include water, such as deionized water, pure water, etc.

[0079] In some embodiments, a three-electrode system can be used to electrochemically corrode the copper alloy substrate using a corrosive solution as an electrolyte, wherein the copper alloy substrate is a working electrode, the AgCl / Ag electrode is a reference electrode, and the platinum electrode is a counter electrode.

[0080] In some embodiments, the voltage between the copper alloy substrate and the reference electrode may be -0.70V to -0.15V.

[0081] In some embodiments, the temperature for electrochemically corroding the copper alloy substrate using the corrosive liquid as the electrolyte may be 10° C.-65° C., and may be optionally 20° C.-35° C.

[0082] In some embodiments, the time for electrochemically corroding the copper alloy substrate using the corrosive liquid as the electrolyte may be 3 hours to 24 hours, and may be 6 hours to 10 hours.

[0083] In some embodiments, the preparation method may further include the step of: rinsing the copper alloy substrate with a corrosive solution.

[0084] In some embodiments, the preparation method may further include the steps of: washing the three-dimensional porous copper after electrochemical corrosion with water, washing with alcohol, and drying. Washing with water can remove soluble salts in the three-dimensional porous copper structure, and washing with alcohol can remove residual moisture in the three-dimensional porous copper structure.

[0085] The number of water washing and alcohol washing is not specifically limited, and the washing time is not specifically limited.

[0086] Optionally, anhydrous ethanol may be used for alcohol washing.

[0087] The embodiment of the present application also provides a three-dimensional porous copper prepared by the above preparation method.

[0088] In some embodiments, the diameter of the holes of the three-dimensional porous copper may be 0.3 μm-20 μm, and may be 2 μm-8 μm.

[0089] In some embodiments, the ligament width of the three-dimensional porous copper may be 0.5 μm-20 μm, and optionally 2 μm-8 μm.

[0090] In some embodiments, the non-Cu metal residue (atomic percentage) of the three-dimensional porous copper may be less than or equal to 5 at.%, and may be less than or equal to 2 at.%.

[0091] Example

[0092] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0093] Preparation of copper alloy substrate

[0094] The Mn75Cu25 alloy was prepared by feeding materials according to Mn:Cu=75:25 (at%), and the smelting method was vacuum induction melting. The smelted CuMn alloy was cut into 3mm alloy blocks, cold rolled to a thickness of about 0.25mm, and then annealed in an argon atmosphere at a temperature of 400℃-700℃ for 6h.

[0095] The annealed CuMn alloy was cut into alloy sheets of 32.0 mm × 25.0 mm in size, and the surface of the CuMn alloy was polished to brightness with 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh sandpaper, respectively. Then, it was ultrasonically cleaned in 200 ml of deionized water and 200 ml of ethanol for 20 seconds, respectively, and then vacuum-baked at 25°C for 1 hour to obtain a CuMn alloy sheet with a clean and bright surface.

[0096] Example 1

[0097] Weigh NaCl and citric acid in batches and add them to 400g of deionized water, stirring continuously to completely dissolve them, then transfer the solution to a 500ml volumetric flask, add deionized water to make the volume 500ml, and obtain a corrosion solution. The concentration of NaCl is 1mol / L, and the concentration of citric acid is 0.12mol / L.

[0098] Rinse the platinum electrode (counter electrode), AgCl / Ag reference electrode, platinum electrode clip, and electrolytic cell with 300 ml of deionized water, and dry the remaining water with dust-free paper. Then rinse the above parts with 50 ml of the above etching solution for 3 times, and then transfer the remaining 300 ml of etching solution to the corrosion tank.

[0099] The CuMn alloy sheet is fixed on the platinum electrode clip, and the electrodes are arranged in the order of the platinum electrode clip (working electrode), the AgCl / Ag reference electrode, and the platinum electrode (counter electrode), so that the electrodes are at the same height, that is, about 1 / 2 of the height of the electrolytic cell. The above three electrodes are connected to the electrochemical workstation, so that the CuMn alloy sheet and the platinum electrode form a working circuit, and the CuMn alloy sheet and the AgCl / Ag reference electrode form a reference circuit.

[0100] The constant potential method was used in the electrochemical dealloying process, the voltage difference between the CuMn alloy sheet and the AgCl / Ag reference electrode was -0.2 V, and the corrosion time was set to 8 hours. After the corrosion reaction, the CuMn alloy sheet turned from silvery white to copper.

[0101] The three-dimensional porous copper sheet was removed and soaked in 200 ml of deionized water for three times, each time for 10 min, to wash away the soluble salts remaining in the three-dimensional porous copper sheet; then the three-dimensional porous copper sheet was soaked in 100 ml of anhydrous ethanol for two times, each time for 5 min, to wash away the residual water in the three-dimensional porous copper sheet; finally, the three-dimensional porous copper sheet was transferred to a vacuum drying oven and baked in an environment of 30°C and -0.1 MPa for 4 hours.

[0102] Examples 2 to 17

[0103] The preparation method of the three-dimensional porous copper sheet is similar to that of Example 1, except that the composition and / or concentration of the etching solution is different. The specific parameters are shown in Table 1.

[0104] Comparative Examples 1 to 6

[0105] The preparation method of the three-dimensional porous copper sheet is similar to that of Example 1, except that the composition and / or concentration of the etching solution is different, and the specific parameters are shown in Table 1. In Table 1, / indicates that the corresponding component is not added to the etching solution.

[0106] Performance Testing

[0107] (1) Surface morphology test of three-dimensional porous copper sheet

[0108] The surface morphology of the three-dimensional porous copper sheet is tested by a scanning electron microscope, and the testing instrument may be a ZEISS sigma 300.

[0109] (2) Mn Residue Test of Three-Dimensional Porous Copper Sheet

[0110] The atomic percentage of residual Mn in the three-dimensional porous copper sheet was measured by inductively coupled plasma atomic emission spectroscopy (ICP).

[0111] (3) Porosity test of three-dimensional porous copper sheet

[0112] The length, width and thickness of the three-dimensional porous copper sheet were measured by a spiral micrometer, and the mass of the three-dimensional porous copper sheet was weighed by an analytical balance. To reduce the measurement error, three different areas were selected for measurement of the length and width of the three-dimensional porous copper sheet, and the average value was taken; five different areas were selected for measurement of the thickness of the three-dimensional porous copper sheet, and the average value was taken; the mass of the three-dimensional porous copper sheet was weighed three times and the average value was taken.

[0113] The porosity of the three-dimensional porous copper sheet is:

[0114]

[0115] P: porosity of the three-dimensional porous copper sheet.

[0116] m: average mass of the three-dimensional porous copper sheet, in g.

[0117] a: Average length of three-dimensional porous copper sheet, in mm.

[0118] b: Average width of the three-dimensional porous copper sheet, in mm.

[0119] h: average thickness of the three-dimensional porous copper sheet, in mm.

[0120] ρ: True density of pure copper, in g / cm 3 .

[0121] The test results are shown in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] From the test results in Table 1, it can be seen that by adjusting the corrosion solution to include a neutral salt and a weakly acidic chelating agent, and adjusting the molar concentration C1 of the neutral salt and the molar concentration C2 of the weakly acidic chelating agent to satisfy 0.04≤C2 / C1≤0.60 and C2 less than or equal to 0.20 mol / L, a stable corrosion environment can be provided, thereby reducing the precipitation reaction of manganese ions dissolved during the electrochemical dealloying process, thereby reducing the pore blocking problem and surface passivation problem of the prepared three-dimensional porous copper, and further improving the porosity of the prepared three-dimensional porous copper sheet; at the same time, crack formation can also be reduced. Figures 1 to 3 It can be seen that the prepared three-dimensional porous copper sheet has a high porosity. At the same time, there is no obvious solid metal compound particle coverage on the surface of the prepared three-dimensional porous copper sheet, and no obvious cracks (no cracks with a width of more than 5 μm) are formed.

[0126] The molar ratio C2 / C1 of the weak acid complexing agent to the neutral salt in the etching solution prepared in Comparative Example 1 is very small, and the molar concentration C2 of the weak acid complexing agent in the etching solution is also small. At this time, the weak acid complexing agent cannot fully play its role in maintaining the acidity of the electrolyte and complexing manganese ions; in addition, during the electrochemical dealloying process, the electrode will continuously consume hydrogen ions due to hydrogen evolution, so the etching solution near the electrode is easily converted to alkaline, which causes the manganese ions dissolved in the copper alloy matrix to easily form solid metal compound particles and adsorb on the surface of the formed three-dimensional porous copper, which is easy to cause pore blocking and surface passivation problems, and also reduce the porosity of the prepared three-dimensional porous copper sheet. Figure 4 It can be seen that the porosity of the prepared three-dimensional porous copper sheet is low, and the surface of the prepared three-dimensional porous copper sheet is also covered with a large number of solid metal compound particles.

[0127] The etching solution of Comparative Example 2 uses a citric acid solution. Since citric acid itself participates in the chemical dealloying reaction, the concentration of the citric acid solution will continue to decrease during the dealloying process, which will affect the ionic conductivity and dealloying effect of the etching solution, and further reduce the porosity of the three-dimensional porous copper sheet; at the same time, when the etching solution uses a citric acid solution, the electrochemical dealloying rate is relatively slow, while the chemical dealloying rate is relatively fast, which is likely to cause cracks to form. Figure 5 It can be seen that the porosity of the prepared three-dimensional porous copper sheet is low, and cracks are also formed on the surface of the prepared three-dimensional porous copper sheet.

[0128] The etching solution of Comparative Example 3 uses a neutral salt and acetic acid solution. Acetic acid is a monobasic acid. When the molar concentration is the same, it can dissociate fewer hydrogen ions. At the same time, acetic acid itself does not have the function of complexing manganese ions. Therefore, during the electrochemical dealloying process, the manganese ions dissolved in the copper alloy matrix are easily formed into solid metal compound particles and adsorbed on the surface of the formed three-dimensional porous copper. Figure 6 It can be seen that the porosity of the prepared three-dimensional porous copper sheet is low, and the surface of the prepared three-dimensional porous copper sheet is also covered with a large number of solid metal compound particles.

[0129] The molar ratio C2 / C1 of the weakly acidic complexing agent to the neutral salt in the etching solution prepared in Comparative Example 4 is relatively large. At this time, the rate of the electrochemical dealloying reaction is relatively slow, and the copper alloy matrix is ​​not completely dealloyed, which results in a low porosity of the prepared three-dimensional porous copper sheet. At the same time, the molar concentration C1 of the neutral salt in the etching solution is still relatively small, and the dealloying reaction of the copper alloy matrix is ​​mainly a chemical corrosion reaction, which is also easy to cause crack formation. Figure 7 It can be seen that the porosity of the prepared three-dimensional porous copper sheet is low, and cracks are also formed on the surface of the prepared three-dimensional porous copper sheet.

[0130] In the etching solution prepared in Comparative Example 5, the molar ratio C2 / C1 of the weakly acidic complexing agent to the neutral salt is small and the molar concentration C1 of the neutral salt is large. At this time, the rate of the electrochemical dealloying reaction is fast, and a large stress is formed in the copper alloy matrix, resulting in obvious cracks in the prepared three-dimensional porous copper sheet. Figure 8 It can be seen that large cracks are formed on the surface of the prepared three-dimensional porous copper sheet.

[0131] The molar concentration C2 of the weakly acidic complexing agent in the etching solution prepared in Comparative Example 6 is relatively large, which may cause a violent chemical dealloying reaction and easily lead to the formation of hydrogen embrittlement cracks. Fig. 9 It can be seen that large cracks are formed on the surface of the prepared three-dimensional porous copper sheet.

[0132] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing three-dimensional porous copper, characterized in that: The steps include: Providing a copper alloy matrix, wherein the copper alloy matrix includes a Cu element and a non-Cu metal element, wherein the standard electrode potential of the non-Cu metal element is lower than the standard electrode potential of the Cu element; Providing a corrosive solution, wherein the corrosive solution comprises a neutral salt, a weakly acidic complexing agent and a solvent, wherein the molar concentration of the neutral salt is recorded as C1, and the molar concentration of the weakly acidic complexing agent is recorded as C2, both in mol / L, 0.04≤C2 / C1≤0.60, and C2 is less than or equal to 0.20 mol / L; The copper alloy substrate is electrochemically corroded by using the corrosive solution as an electrolyte to obtain three-dimensional porous copper.

2. The preparation method according to claim 1, characterized in that: 0.10≤C2 / C1≤0.

24.

3. The preparation method according to any one of claims 1 to 2, characterized in that: C1 is 0.2mol / L-2.0mol / L, and can be optionally 0.5mol / L-1.5mol / L; and / or, C2 is 0.04mol / L-0.20mol / L, and can be optionally 0.08mol / L-0.16mol / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that The neutral salt includes one or more of sodium salt and potassium salt, and may optionally include one or more of sodium chloride and potassium chloride; and / or, The weakly acidic complexing agent includes one or more of dicarboxylic acids, polycarboxylic acids, and their respective salts, and may be selected from citric acid, isocitric acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, fumaric acid, and their respective salts. Optionally, the salt includes one or more of sodium salt, potassium salt, sodium potassium salt, and ammonium salt; and / or, The solvent includes water.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The copper alloy substrate is electrochemically corroded by using a three-electrode system with the corrosive solution as an electrolyte, the copper alloy substrate is a working electrode, the AgCl / Ag electrode is a reference electrode, and the platinum electrode is a counter electrode.

6. The preparation method according to claim 5, characterized in that: The voltage between the copper alloy substrate and the reference electrode is -0.70V to -0.15V.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature for electrochemically corroding the copper alloy substrate using the corrosive solution as an electrolyte is 10° C.-65° C., and can be optionally 20° C.-35° C.; and / or, The time for electrochemically corroding the copper alloy substrate using the corrosive solution as the electrolyte is 3h-24h, and can be optionally 6h-10h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The copper alloy substrate is in the form of a sheet or foil; and / or, The non-Cu metal elements include one or more of Mn, Zn, Ni, Al, and Fe.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The preparation method further comprises the step of: using a corrosive liquid to rinse the copper alloy substrate.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The preparation method also includes the steps of: washing the three-dimensional porous copper after electrochemical corrosion with water, washing with alcohol and drying.

11. The preparation method according to any one of claims 1 to 10, characterized in that: The atomic percentage of the non-Cu metal elements in the copper alloy matrix is ​​greater than 65 at.%, and can be selected to be 65 at.%-80 at.%.

12. A three-dimensional porous copper prepared by the preparation method according to any one of claims 1 to 11.

13. The three-dimensional porous copper according to claim 12, characterized in that: The pore diameter of the three-dimensional porous copper is 0.3 μm-20 μm, and can be 2 μm-8 μm; and / or, The ligament width of the three-dimensional porous copper is 0.5 μm-20 μm, and can be 2 μm-8 μm; and / or, The non-Cu metal residue in the three-dimensional porous copper is less than or equal to 5 at.%, and can be less than or equal to 2 at.%.

Citation Information

Cited By

  • Three-dimensional porous copper and preparation method therefor

    EP4621110A1